Internal Phosphorus Loading from the Bottom Sediments of a Dimictic Lake During Its Sustainable Restoration - Kowalczewska-Madura, Katarzyna (Water Air Soil Pollut, 2018)
The ribbon type Lake Durowskie (Western Poland) is currently undergoing a sustainable restoration process due to water quality deterioration, manifested in water blooms, low transparency, and oxygen deficits near the bottom sediments. Three restoration methods were applied: (i) hypolimnion aeration using two wind-driven pulverizing aerators installed at the deepest places, (ii) phosphorus inactivation using small doses of iron sulfate and magnesium chloride several times a year, and (iii) biomanipulation using pike fry stocking. Research on the exchange of phosphorus in the sediment-water interphase was conducted in the years 2009–2016 to determine the multiannual changes of internal phosphorus loading from bottom sediments during the restoration process. The sustainable approach resulted in a decrease of internal phosphorus loading and a gradual increase in the sorption capacity of bottom sediments, particularly noticeable in the last 2 years. The content of phosphorus in the sediment and in the interstitial water fluctuated, showing an increase during the first years of restoration and then a gradual decrease. It was proved that the process of sustainable restoration is cheap and does not interfere strongly with the ecosystem, although it is long-lasting. It should be continued for many years, especially in the case of continuous external loading of the lake with nutrients from the catchment area, i.e., until the water quality in the main tributary improves and the lake ecosystem stabilizes.